Exploring the role of stearic acid in modified zinc aluminum layered double hydroxides and their acrylonitrile butadiene rubber nanocomposites. Issue 9 (18th October 2014) - Eshwaran, Subramani Bhagavatheswaran; Basu, Debdipta; Vaikuntam, Sankar Raman; Kutlu, Burak; Wiessner, Sven; Das, Amit; Naskar, Kinsuk; Heinrich, Gert
ABSTRACT The proposed study attempted to explore the role of stearic acid modification on the properties of zinc‐aluminum based layered double hydroxides (LDH) and their composites with acrylonitrile butadiene rubber (NBR). Three distinctive LDH systems were adapted for such comparison; an unmodified LDH and two stearic acid modified LDH. The use of zinc oxide and stearic acid in the rubber formulation was avoided as the modified LDH would be able to deliver the necessary activators for the vulcanization process. Emphasis was predominantly given to reconnoiter the merits of stearic acid modification on the increase in interlayer distance of the LDH. X‐ray diffraction studies and transmission electron microscope morphological investigations of LDH powders indicated that modification with stearic acid increased the interlayer spacing which would favor the intercalation of NBR polymer chains into the layered space. However, stress–strain studies indicated better mechanical properties for composites with unmodified LDH. Composites with LDH showed higher crosslinking densities than conventionally sulfur cured control compounds using zinc oxide/stearic acid as activators. This was evident from equilibrium swelling method as well as statistical theory of rubber elasticity. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41539.